A Comparative Study of Liquid-Based Cytology and DNA Image Cytometry in the Diagnosis of Serous Effusion. (27th August 2020) - Wang, Shaohua; Li, Dan; Wang, Jieqiong; Wan, Yu; Huang, Conggai; Yang, Bo; Tang, Xiaoqin; Tian, Gang; Yang, Zhihui
Background: Liquid-based cytology is one of the most useful methods to diagnose a patient with serous effusion, especially when malignancy is suspected. As an alternative to the use of liquid-based cytology only, the serous effusion can be further processed using the technique of DNA image cytometry, which may augment diagnostic utility. The aim of this study was to compare the diagnostic yields of liquid-based cytology, DNA image cytometry, and both in combination, regardless of serous-effusion etiology. Methods: We conducted a descriptive study on patients with serous effusions from July 2016 to June 2018. All samples were submitted for liquid-based cytology and DNA image cytometry techniques. We compared the results of cytopathological studies to the final diagnoses. Results: For a total of 798 samples, final diagnoses included 412 (51.6%) malignancies, 280 (35.1.%) inflammatory diseases, and 106 (13.3%) transudative serous effusions. Liquid-based cytology had a more sensitive diagnostic yield than DNA image cytometry did (38.8% vs 30.7%; P < .05), but the combination of both had a higher yield (43.7%; P < .05) compared with that of liquid-based cytology alone. For the 412 malignant serous effusions, diagnostic yields of liquid-based cytology and DNA image cytometry were 73.8% and 59.5%, respectively. The difference in sensitivity was significant ( P < .05). Combined liquid-based cytology + DNA image cytometry improved diagnostic yield to 83.3% ( P < .05). However, both liquid-based cytology and DNA image cytometry had low diagnostic yields for inflammatory diseases and transudative serous effusions. Conclusion: In serous effusion, liquid-based cytology's diagnostic performance is better than that of DNA image cytometry. Application of both techniques can significantly increase diagnostic yield.